Interatomic relaxation effects in double core ionization of chain molecules - Kryzhevoi, Nikolai V.; Cederbaum, Lorenz S. (The journal of chemical physics, 2012)
Core vacancies created on opposite sides of a molecule operate against each other in polarizing the environment between them. Consequently, the relaxation energy associated with the simultaneous creation of these two core holes turns out to be smaller than the sum of the relaxation energies associated with each individual single core vacancy created independently. The corresponding residual, termed interatomic relaxation energy, is sensitive to the environment. In the present paper we explore how the interatomic relaxation energy depends on the length and type of carbon chains bridging two core ionized nitrile groups (-C≡N). We have uncovered several trends and discuss them with the help of simple electrostatic and quantum mechanical models. Namely, the absolute value of the interatomic relaxation energy depends strongly on the orbital hybridization in carbons being noticeably larger in conjugated chains (sp and sp2 hybridizations) possessing highly mobile electrons in delocalized π-type orbitals than in saturated chains (sp3 hybridization) where only σ bonds are available. The interatomic relaxation energy decreases monotonically with increasing chain length. The corresponding descent is determined by the energetics of the molecular bridge, in particular, by the HOMO-LUMO gap. The smallest HOMO-LUMO gap is found in molecules with the sp2-hybridized backbone. Here, the interatomic relaxation energy decreases slowest with the chain length.